PENGARUH KEGIATAN ROLE PLAYING WITH MUSIC TERHADAP PENGEMBANGAN KARAKTER SOCIAL CARE ANAK DI TK - Besmah, Amelia Anggun; Eliza, Delfi; Mahyuddin, Nenny; Izzati, Izzati (Jurnal Warna, 2019)
This study aims to look at the effect of role playing with music activities on the development of children’s social care in kindergardeten. Role playing with music itself is a role playing activity using music so that the development of children’s social care. The method in this study uses quantitative with experimental quasy types. The test is used as a data collection technique, in the form of a 5-point statement, then the data is processed using a difference test (t-test). The results of the data analysis of the experimental group got on average using 79,25 role playing activities with music and 70,93 control groups with micro role playing activities. The results of this study can be concluded that the role playing with music activities affect the development of social care (social care) children in Islamic Kindergarten Khaira Ummah Padang.